THE APPLICATION OF KIND OF CLASSROOM TEACHING CONTEXTUAL LEARNING ( CTL) THROUGH THE USE OF GOOGLE CLASSROOM FOR A PANDEMIC COVID 19 ECONOMICS TEACHER IN HIGH SCHOOL STUDENTS TAMAN SISWA PADANG - Stevani Stevani; Vivina Eprillison; Meri Rahmania; Yuli Diniah Zulbakri (STKIP PGRI Sumatera Barat, 2020)
One of the media learning and an evaluation tool required teachers in the pendemi covid 19 this is google application that can be used classroom teachers in free in the learning process in the tissues .Google is a series of classroom produktivtas tools from google gmail are free , drive , and docs , made available to users google apps for education .Designed to help teachers or classroom teachers make and collect duty without using paper , including a feature to save time teachers like the ability to make a copy google docs automatically for each student .Classroom can also make folder drive for any task and each student , that they were still regularly .The desire to achieve in doing this is to provide humbling experience for teachers in using google online class which is very useful in the classroom covid 19 this pandemic